E-learning Challenges in the Era of Covid-19: The Georgian Case - Kakutia, Tamar; Hunt, Elena; Butakor, Paul Kwame; Muhammad Shah, Syed Mir (European Scientific Journal, ESJ, 2023)
Digital literacy became an essential skill for learning, living and working. Therefore, the Internet remains a main part of modern life, constantly evolving and facilitating peopleâ€™s lives. The global Covid-19 pandemic has made the issue of effective use of information and communication tools and proper possession of digital skills and its importance even more urgent. Higher education around the world has largely shifted to a distance/online-learning format. Covid-19 pandemic has affected many countries on a large scale, and Georgia’s higher education system was no exception. Due to the wide-scale spread of the virus and in order to reduce the disastrous consequences, the state decided to continue education throughout Georgia remotely through online learning platforms, which posed a number of challenges for representatives of higher education institutions, as well as academic staff and students. The transition to online teaching has also created problems in the process of fully implementing student support activities. As the university mandates the creation of a student-friendly environment, to offer relevant services, to inform and support students with low social status and students with disabilities, it became a great challenge for Georgian universities to provide socially disadvantaged students with the resources needed for E-learning. The study is about Georgian case, how effective Georgian government managed learning prosses in the period of Covid-19 pandemic; What kind of challenges students had in this period and what are their vision regarding the online learning and its perspective for future development of teaching/studying process.